Fairness and Smiling Mediate the Effects of Openness on Perceived Fairness: Beside Perceived Intention - He, Zhifang; Liu, Jianping; Rao, Zhiming; Wan, Lili (Frontiers in Psychology, 2018)
Previous studies have shown that smiling, fairness, intention, and the results being openness to the proposer can influence the responses in ultimatum games, respectively. But it is not clear that how the four factors might interact with each other in twos or in threes or in fours. This study examined the way that how the four factors work in resource distribution games by testing the differences between average rejection rates in different treatments. Two hundred and twenty healthy volunteers participated in an intentional version of the ultimatum game (UG). The experiment used a 2 × 2 × 2 × 2 mixed design with “openness” as a between subjects factor and the other three as within subjects factors, and the participants were assigned as recipients. The results revealed that fairness or perceived good intention reduced the subject’s average rejection rates. There was a significant interaction between facial expressions and openness. With fair offers, the average rejection rate for informed was lower than that of uninformed; but when unfair, no difference between the corresponding average rejection rates was found. The interaction effect of smiling and openness was also significant, the average rejection rate for informed offers was lower when the proposer was smiling and no rejection rate difference between uninformed offers and informed offers when no smiling. No other interaction effect was found.